Some Topological Indices of Double Square Snake Graphs - Mahalank, Pushpalatha; Majhi, Bhairaba Kumar; Cangul, Ismail Naci (The Nepali Mathematical Sciences Report, 2021)
In many areas of science, lattice structures are very useful phenomenons. In network sciences, in chemistry and in social sciences, we face them in the solution of many daily life problems. Several large lattice structures can also be thought as graphs and in that way, are useful in the study of large networks. A very recently defined and studied class of such networks are snake graphs which has close relations with number theory due to the use of continued fractions. Following the works on square snake graphs, in this work, we study some non-Zagreb type topological graph indices of some interesting lattice structures called as double square snake graphs. We first obtain the vertex and edge partitions of these graphs and calculate their indices by means of these partitions.